Efficacy and safety of cotadutide, a dual glucagon‐like peptide‐1 and glucagon receptor agonist, in a randomized phase 2a study of patients with type 2 diabetes and chronic kidney disease. Issue 7 (25th April 2022) - Parker, Victoria E. R.; Hoang, Thuong; Schlichthaar, Heike; Gibb, Fraser W.; Wenzel, Barbara; Posch, Maximillian G.; Rose, Ludger; Chang, Yi‐Ting; Petrone, Marcella; Hansen, Lars; Ambery, Philip; Jermutus, Lutz; et al.
Abstract: Aim: To assess the efficacy, safety and tolerability of cotadutide in patients with type 2 diabetes mellitus and chronic kidney disease. Materials and Methods: In this phase 2a study (NCT03550378), patients with body mass index 25‐45 kg/m 2, estimated glomerular filtration rate 30‐59 ml/min/1.73 m 2 and type 2 diabetes [glycated haemoglobin 6.5‐10.5% (48‐91 mmol/mol)] controlled with insulin and/or oral therapy combination, were randomized 1:1 to once‐daily subcutaneous cotadutide (50‐300 μg) or placebo for 32 days. The primary endpoint was plasma glucose concentration assessed using a mixed‐meal tolerance test. Results: Participants receiving cotadutide (n = 21) had significant reductions in the mixed‐meal tolerance test area under the glucose concentration‐time curve (–26.71% vs. +3.68%, p  < .001), more time in target glucose range on continuous glucose monitoring (+14.79% vs. –21.23%, p  = .001) and significant reductions in absolute bodyweight (–3.41 kg vs. –0.13 kg, p  < .001) versus placebo (n = 20). In patients with baseline micro‐ or macroalbuminuria (n = 18), urinary albumin‐to‐creatinine ratios decreased by 51% at day 32 with cotadutide versus placebo ( p  = .0504). No statistically significant difference was observed in mean change in estimated glomerular filtration rate between treatments. Mild/moderate adverse events occurred in 71.4% of participants receiving cotadutide and 35.0% receiving placebo. Conclusions: We established the efficacy of cotadutide in this patient population, with significantly improved postprandial glucose control and reduced bodyweight versus placebo. Reductions in urinary albumin‐to‐creatinine ratios suggest potential benefits of cotadutide on kidney function, supporting further evaluation in larger, longer‐term clinical trials.